Design and structural analysis of a 100 kg/h palm frond shaving machine using SolidWorks - Dicky Septri Anugrah; Achmad Jusuf Zulfikar; Ibnu Hajar; Suardi (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
This study presents the design and structural analysis of a palm frond shaving machine with a production capacity of 100 kg/hour, aimed at improving the efficiency of the traditional manual process used by craftsmen. The manual method is time-consuming and labor-intensive, limiting production to approximately 2 kg/hour. To address this issue, a mechanical design was developed using SolidWorks 2017 software. The research involved consumer surveys to identify user requirements, followed by concept generation, technical and economic evaluation, and simulation analysis of the selected design. Among three design variants, the second concept—featuring a stone grinder cutter system, UNP steel frame, V-belt transmission, and gasoline engine—was selected as optimal based on combined technical and economic scores. Structural simulation results indicate that the frame, made from UNP 50 steel profiles, exhibits acceptable stress, displacement, and safety factor levels under an applied load of 10 kg. This study offers a viable solution for small-scale industries to process palm fronds into usable sticks efficiently. Future work may include prototype development and extended performance testing. The machine’s application is expected to contribute to local economies by utilizing agricultural waste and increasing the production of palm stick-based handicrafts.